Asymmetric thermo-electric aerogel as well as preparation method and application thereof
By using the preparation method of asymmetric thermoelectric gels in thermoelectric materials, the synergistic effects of bismuth telluride, poly(3,4-ethylenedioxythiophene), MXene and bacterial cellulose are solved, and efficient thermoelectric conversion and structural stability are achieved.
Patent Information
- Application Number
- CN202510191689.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-21
AI Technical Summary
The thermal energy and electrical energy conversion efficiency of existing thermoelectric materials is low, mainly due to the poor binding of nanomaterials to bacterial cellulose, resulting in increased agglomeration and brittleness.
The preparation method of asymmetric thermoelectric gels is adopted. By mixing bismuth telluride powder with bacterial cellulose dispersion, the lower gel is formed, and poly(3,4-ethylenedioxythiophene), MXene and bacterial cellulose dispersion are mixed to form the upper gel. The two layers of gels are processed by ultra-low temperature freezing technology and vacuum freeze-drying technology to form an asymmetric thermoelectric gel.
Through the synergistic effect of the upper and lower layers of gels, the efficient conversion of thermoelectric to electrical energy is achieved, the thermoelectric conversion efficiency is improved, and the stability of the aerogel structure is enhanced.
Smart Images

Figure CN119698217A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aerogel preparation, and relates to a method for preparing an aerogel, in particular to an asymmetric thermoelectric gel and a preparation method and application thereof. Background Art
[0002] Thermoelectric power generation is a new energy technology that converts waste heat in nature into electrical energy. It has broad application prospects. As a result, various thermoelectric materials have emerged. However, current thermoelectric materials have the problem of low efficiency in converting heat energy into electrical energy.
[0003] Chinese invention patent CN 109301060 B "A method for preparing a composite aerogel thermoelectric material" uses poly (3, 4-ethylenedioxythiophene) (PEDOT) organic conductive polymer materials and nanomaterials such as carbon nanotubes to improve the thermoelectric conversion efficiency. However, although the conductivity and Seebeck coefficient in this patent have been improved to a certain extent, the improvement is limited. Overall, the thermoelectric conversion efficiency is still low. This is because nanomaterials such as carbon nanotubes have no active groups and cannot be well combined with bacterial cellulose. They are prone to agglomeration, which affects the thermoelectric conversion efficiency of the aerogel material. In addition, it may also increase the brittleness of the aerogel. Therefore, it is of great significance to develop a thermoelectric material with high thermoelectric conversion efficiency. Summary of the invention
[0004] In view of the above technical difficulties, the present invention provides an asymmetric thermoelectric gel and a preparation method and application thereof.
[0005] In order to solve the above technical problems, the present invention is implemented through the following technical solutions: One of the objects of the present invention is to provide a method for preparing an asymmetric thermoelectric gel, the method comprising: S1, preparing a lower layer gel: mixing bismuth telluride powder and bacterial cellulose dispersion evenly to obtain a mixed solution 1, wherein the mixed solution 1 contains bismuth telluride and bacterial cellulose, then adding a cross-linking agent to the mixed solution 1, stirring at room temperature to form a gel, and pouring the gel into a mold to obtain a lower layer gel; S2, preparing an upper gel: uniformly mixing poly(3,4-ethylenedioxythiophene), MXene and bacterial cellulose dispersion to obtain a mixed solution 2, wherein the mixed solution 2 contains poly(3,4-ethylenedioxythiophene), MXene and bacterial cellulose, and then adding a crosslinking agent to the mixed solution 2, stirring at room temperature to form a gel, and pouring the gel onto the lower gel in the mold described in S1 to form an upper gel, thereby obtaining an asymmetric double-layer gel; S3, preparing a double-layer aerogel precursor: using ultra-low temperature freezing technology to treat an asymmetric double-layer gel to obtain a double-layer aerogel precursor; S4. Preparation of asymmetric thermoelectric gel: vacuum freeze-drying technology is used to dry and solidify the double-layer aerogel precursor to obtain an asymmetric thermoelectric gel.
[0006] It is further defined that the asymmetric thermoelectric gel is obtained by treating an asymmetric double-layer gel with ultra-low temperature freezing technology and vacuum freeze-drying technology, and the upper gel and the lower gel in the asymmetric double-layer gel are prepared using different materials.
[0007] It is further defined that the contents of bismuth telluride and bacterial cellulose in the mixed solution 1 of S1 are 10-20wt% and 50-80wt%, respectively.
[0008] It is further defined that the contents of poly(3,4-ethylenedioxythiophene), MXene and bacterial cellulose in the mixed solution 2 of S2 are 1~3wt%, 0.5~2wt% and 50~80wt%, respectively.
[0009] It is further defined that the stirring time in S1 and S2 is 3 to 6 hours.
[0010] It is further defined that the cross-linking agents in S1 and S2 are chemical reagents that can promote the cross-linking reaction between bacterial cellulose molecules.
[0011] It is further defined that the cross-linking agent in S1 is glutaraldehyde, epichlorohydrin or polyethylene glycol diglycidyl ether; and the cross-linking agent in S2 is glutaraldehyde, epichlorohydrin or polyethylene glycol diglycidyl ether.
[0012] It is further defined that the amount of the cross-linking agent in S1 is 10 wt % of the bacterial cellulose content in the mixed solution 1 of S1; and the amount of the cross-linking agent in S2 is 10 wt % of the bacterial cellulose content in the mixed solution 2 of S2.
[0013] It is further specified that the ultra-low temperature freezing technology temperature in S3 is -80~-40℃ and the time is 24~48h.
[0014] It is further defined that the time for the drying and solidification treatment using vacuum freeze-drying technology in S4 is 24 to 72 hours.
[0015] A second object of the present invention is to provide an asymmetric thermoelectric gel prepared by the above method.
[0016] The third object of the present invention is to provide an application of the above-mentioned asymmetric thermoelectric gel as a thermoelectric material in the field of thermoelectric conversion.
[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention first prepares a lower gel and an upper gel. The two gels form an asymmetric double-layer gel in a mold. After being treated with ultra-low temperature freezing technology and vacuum freeze drying technology, the upper gel becomes an upper aerogel, and the lower gel becomes a lower aerogel. The substance composed of the two layers of aerogel is an asymmetric thermoelectric gel. The asymmetry in the asymmetric thermoelectric gel refers to the upper and lower gel layers being made of different materials. Therefore, the materials of the upper and lower aerogel layers formed are also different, that is, the upper and lower layers of the asymmetric thermoelectric gel are made of different materials. When the side of the asymmetric thermoelectric gel containing bismuth telluride is heated by a heat source, the heat is effectively transferred to the inside of the aerogel through the porous structure of bacterial cellulose, and bismuth telluride (Bi2Te3) converts the absorbed heat into electrical energy by using its thermoelectric effect. MXene (two-layered nanomaterial) and PEDOT in the upper aerogel provide an effective charge conduction path. Due to the excellent conductivity of MXene, the thermoelectric charge generated by the lower Bi2Te3 is collected and conducted, so that the electrical energy can be more effectively extracted and utilized. Therefore, the conversion of thermoelectric to electrical energy is achieved through the synergistic effect between the upper and lower aerogel layers. The lower layer Bi2Te3 is responsible for thermoelectric conversion, the upper layer MXene and PEDOT are responsible for charge collection and conduction, and bacterial cellulose, as a porous skeleton material, promotes heat transfer and enhances the stability of the asymmetric thermoelectric gel structure.
[0018] (2) In the lower layer aerogel of the asymmetric thermoelectric gel provided by the present invention, the amount of bismuth telluride plays a key role in the thermoelectric conversion efficiency. When the amount of bismuth telluride is too low, the active sites involved in the thermoelectric conversion are insufficient, resulting in the inability to fully convert the absorbed heat into electrical energy, and the thermoelectric conversion efficiency is significantly reduced. On the contrary, if the amount of bismuth telluride is too high, too much bismuth telluride will cause the internal structure of the aerogel material to become dense, hindering the heat from being transferred to the interior of the aerogel through the porous structure of bacterial cellulose, which is also not conducive to improving the thermoelectric conversion efficiency.
[0019] (3) In the upper aerogel of the asymmetric thermoelectric gel provided by the present invention, MXene and PEDOT are key substances for charge conduction, and their dosage is also very important. MXene is responsible for collecting and conducting the thermoelectric charges generated by the lower layer of bismuth telluride with its excellent conductivity. If the dosage of MXene is insufficient, an effective charge conduction network cannot be formed, and the generated electrical energy is difficult to be efficiently extracted and utilized, thereby reducing the overall thermoelectric conversion efficiency of the asymmetric thermoelectric gel material. However, when the dosage of MXene is too high, it will affect its synergistic effect with PEDOT and other materials, resulting in uneven charge distribution inside the asymmetric thermoelectric gel, which will also have an adverse effect on thermoelectric conversion and reduce the thermoelectric conversion efficiency. If the dosage of PEDOT is too low, the charge conduction efficiency is low, and it cannot conduct charges well with MXene, which will cause the charge conduction path to be "broken", making it impossible for the electrical energy generated by thermoelectric conversion to be smoothly conducted. However, if the amount of PEDOT is too high, it will destroy the porous structure of the upper aerogel and change the interface properties between the aerogel materials, thereby hindering the synergistic effect between MXene, PEDOT and bacterial cellulose, and further reducing the thermoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a photo of the asymmetric thermoelectric gel prepared in Example 1; Figure 2 This is a SEM image of the asymmetric thermoelectric gel prepared in Example 1; Figure 3 This is a SEM image of the thermoelectric gel prepared in Comparative Example 1; Figure 4 This is a SEM image of the thermoelectric gel prepared in Comparative Example 2; Figure 5 Schematic diagram of the Seebeck coefficient testing method of the thermoelectric gels prepared in Examples 1 to 12 and Comparative Examples 1 to 7. DETAILED DESCRIPTION
[0021] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in combination with the embodiments of the specification. In the following description, many specific details are elaborated to facilitate a full understanding of the present invention, but the present invention can also be implemented in other ways different from those described herein. Those skilled in the art can make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0022] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0023] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0024] The bacterial cellulose dispersion in the following examples and comparative examples was purchased from Guilin Sailun Technology Co., Ltd., model BCS60N, and MXene was purchased from Xinen Technology Co., Ltd.
[0025] Example 1 S1. preparing a lower layer gel: uniformly mixing Bi2Te3 powder and bacterial cellulose dispersion to obtain a mixed solution 1, wherein the contents of bismuth telluride and bacterial cellulose in the mixed solution 1 are 10wt% and 60wt%, respectively; then adding a crosslinking agent glutaraldehyde to the mixed solution 1, wherein the amount of glutaraldehyde is 10wt% of the bacterial cellulose content in the mixed solution 1; stirring at room temperature for 4h to promote the gelation process and form a gel; pouring the formed gel into a mold having a length of 5cm, a width of 3cm, and a height of 2cm to obtain a lower layer gel; and the thickness of the lower layer gel is 1cm; S2, preparing the upper gel: PEDOT, MXene (Ti3AlC2) and bacterial cellulose dispersion are mixed evenly to obtain a mixed solution 2, in which the contents of PEDOT, MXene (Ti3AlC2) and bacterial cellulose are 2wt%, 1.5wt% and 60wt%, respectively; then, a crosslinking agent glutaraldehyde is added to the mixed solution 2, and the amount of glutaraldehyde is 10wt% of the bacterial cellulose content in the mixed solution 2; the mixture is stirred at room temperature for 4h to promote the gelation process and form a gel; the gel is poured onto the lower gel in the mold described in S1 to form an upper gel with a thickness of 1cm, and an asymmetric double-layer gel is obtained; S3, preparing a double-layer aerogel precursor: freezing the asymmetric double-layer gel for 30 hours using an ultra-low temperature freezing technique at -60°C to make it solid, thereby forming a double-layer aerogel precursor; S4. Preparation of asymmetric thermoelectric gel: Using vacuum freeze-drying technology, the double-layer aerogel precursor is dried and solidified for 48 hours to remove moisture in the precursor and obtain an asymmetric thermoelectric gel.
[0026] The SEM image of the asymmetric thermoelectric gel prepared in this example is shown in FIG. Figure 2As shown, it can be seen that the surface of the asymmetric thermoelectric gel is loose and porous, indicating that PEDOT, MXene and Bi2Te3 work synergistically to form a uniform network structure, which helps to improve the thermoelectric performance.
[0027] Example 2 The difference between this embodiment and embodiment 1 is that the content of Bi2Te3 in the mixed solution 1 of S1 is 20wt%, and the remaining process steps and parameter settings are the same as those in embodiment 1.
[0028] Example 3 S1. Prepare the lower gel: Bi2Te3 powder and bacterial cellulose dispersion are mixed evenly to obtain a mixed solution 1, wherein the contents of bismuth telluride and bacterial cellulose in the mixed solution 1 are 15wt% and 60wt%, respectively; then, a crosslinking agent epichlorohydrin is added to the mixed solution 1, and the amount of epichlorohydrin is 10wt% of the bacterial cellulose content in the mixed solution 1; the mixture is stirred at room temperature for 4h to promote the gelation process and form a gel; the formed gel is poured into a mold with a length of 5cm, a width of 3cm, and a height of 2cm to obtain a lower gel; the thickness of the lower gel is 1cm; S2, prepare the upper gel: PEDOT, MXene (Ti3AlC2) and bacterial cellulose dispersion are mixed evenly to obtain mixed solution 2, in which the contents of PEDOT, MXene (Ti3AlC2) and bacterial cellulose are 1wt%, 1.5wt% and 60wt%, respectively; then add crosslinking agent epichlorohydrin to mixed solution 2, the amount of epichlorohydrin is 10wt% of the bacterial cellulose content in mixed solution 2, stir at room temperature for 4h to promote the gelation process, form gel, pour the gel onto the lower gel in the mold described in S1, form an upper gel with a thickness of 1cm, and obtain an asymmetric double-layer gel; S3, preparing a double-layer aerogel precursor: freezing the asymmetric double-layer gel for 30 hours using an ultra-low temperature freezing technique at -60°C to make it solid, thereby forming a double-layer aerogel precursor; S4. Preparation of asymmetric thermoelectric gel: Using vacuum freeze-drying technology, the double-layer aerogel precursor is dried and solidified for 48 hours to remove moisture in the precursor and obtain an asymmetric thermoelectric gel.
[0029] Example 4 The difference between this embodiment and embodiment 3 is that the content of PEDOT in the mixed solution 2 of S2 is 3 wt %, and the remaining process steps and parameter settings are the same as those in embodiment 3.
[0030] Example 5 S1. Prepare the lower gel: Bi2Te3 powder and bacterial cellulose dispersion are mixed evenly to obtain a mixed solution 1, wherein the contents of bismuth telluride and bacterial cellulose in the mixed solution 1 are 15wt% and 60wt%, respectively; then, a crosslinking agent polyethylene glycol diglycidyl ether is added to the mixed solution 1, and the amount of polyethylene glycol diglycidyl ether is 10wt% of the bacterial cellulose content in the mixed solution 1; the mixture is stirred at room temperature for 4h to promote the gelation process and form a gel; the formed gel is poured into a mold with a length of 5cm, a width of 3cm, and a height of 2cm to obtain a lower gel; the thickness of the lower gel is 1cm; S2, prepare the upper gel: PEDOT, MXene (Ti3AlC2) and bacterial cellulose dispersion are mixed evenly to obtain mixed solution 2, in which the contents of PEDOT, MXene (Ti3AlC2) and bacterial cellulose are 2wt%, 0.5wt% and 60wt%, respectively; then, polyethylene glycol diglycidyl ether, a crosslinking agent, is added to the mixed solution 2, and the amount of polyethylene glycol diglycidyl ether is 10wt% of the bacterial cellulose content in the mixed solution 2; the mixture is stirred at room temperature for 4h to promote the gelation process and form a gel; the gel is poured onto the lower gel in the mold described in S1 to form an upper gel with a thickness of 1cm, and an asymmetric double-layer gel is obtained; S3, preparing a double-layer aerogel precursor: freezing the asymmetric double-layer gel for 30 hours using an ultra-low temperature freezing technique at -60°C to make it solid, thereby forming a double-layer aerogel precursor; S4. Preparation of asymmetric thermoelectric gel: Using vacuum freeze-drying technology, the double-layer aerogel precursor is dried and solidified for 48 hours to remove moisture in the precursor and obtain an asymmetric thermoelectric gel.
[0031] Example 6 The difference between this embodiment and embodiment 5 is that the content of MXene (Ti3AlC2) in the mixed solution 2 of S2 is 2wt%, and the remaining process steps and parameter settings are the same as those in embodiment 5.
[0032] Example 7 S1. Prepare the lower gel: Mix Bi2Te3 powder and bacterial cellulose dispersion evenly to obtain a mixed solution 1, wherein the contents of bismuth telluride and bacterial cellulose in the mixed solution 1 are 15wt% and 50wt%, respectively; then add a crosslinking agent, polyethylene glycol diglycidyl ether, to the mixed solution 1, wherein the amount of polyethylene glycol diglycidyl ether is 10wt% of the bacterial cellulose content in the mixed solution 1; stir at room temperature for 4h to promote the gelation process and form a gel; pour the formed gel into a mold having a length of 5cm, a width of 3cm, and a height of 2cm to obtain a lower gel having a thickness of 1cm; S2, prepare the upper gel: PEDOT, MXene (Ti3AlC2) and bacterial cellulose dispersion are mixed evenly to obtain mixed solution 2, in which the contents of PEDOT, MXene (Ti3AlC2) and bacterial cellulose are 2wt%, 1.5wt% and 50wt%, respectively; then, polyethylene glycol diglycidyl ether, a crosslinking agent, is added to the mixed solution 2, and the amount of polyethylene glycol diglycidyl ether is 10wt% of the bacterial cellulose content in the mixed solution 2; the mixture is stirred at room temperature for 4h to promote the gelation process and form a gel; the gel is poured onto the lower gel in the mold described in S1 to form an upper gel with a thickness of 1cm, and an asymmetric double-layer gel is obtained; S3, preparing a double-layer aerogel precursor: freezing the asymmetric double-layer gel for 30 hours using an ultra-low temperature freezing technique at -60°C to make it solid, thereby forming a double-layer aerogel precursor; S4. Preparation of asymmetric thermoelectric gel: Using vacuum freeze-drying technology, the double-layer aerogel precursor is dried and solidified for 48 hours to remove moisture in the precursor and obtain an asymmetric thermoelectric gel.
[0033] Example 8 The difference between this embodiment and embodiment 7 is that the content of bacterial cellulose in the mixed solution 1 of S1 is 80wt%; the mass fraction of bacterial cellulose in the mixed solution 2 of S2 is 80wt%, and the remaining process steps and parameter settings are the same as those in embodiment 7.
[0034] Example 9 S1. Prepare the lower gel: Bi2Te3 powder and bacterial cellulose dispersion are mixed evenly to obtain a mixed solution 1, wherein the contents of bismuth telluride and bacterial cellulose in the mixed solution 1 are 15wt% and 60wt%, respectively; then, a crosslinking agent epichlorohydrin is added to the mixed solution 1, and the amount of epichlorohydrin is 10wt% of the bacterial cellulose content in the mixed solution 1; the mixture is stirred at room temperature for 3h to promote the gelation process and form a gel; the formed gel is poured into a mold with a length of 5cm, a width of 3cm, and a height of 2cm to obtain a lower gel; the thickness of the lower gel is 1cm; S2, prepare the upper gel: PEDOT, MXene (Ti3AlC2) and bacterial cellulose dispersion are mixed evenly to obtain mixed solution 2, in which the contents of PEDOT, MXene (Ti3AlC2) and bacterial cellulose are 2wt%, 1.5wt% and 60wt%, respectively; then, crosslinking agent epichlorohydrin is added to the mixed solution 2, and the amount of epichlorohydrin is 10wt% of the bacterial cellulose content in the mixed solution 2; stir at room temperature for 3h to promote the gelation process and form a gel; pour the gel onto the lower gel in the mold described in S1 to form an upper gel with a thickness of 1cm, and obtain an asymmetric double-layer gel; S3, preparing a double-layer aerogel precursor: freezing the asymmetric double-layer gel for 30 hours using an ultra-low temperature freezing technique at -60°C to make it solid, thereby forming a double-layer aerogel precursor; S4. Preparation of asymmetric thermoelectric gel: Using vacuum freeze-drying technology, the double-layer aerogel precursor is dried and solidified for 48 hours to remove moisture in the precursor and obtain an asymmetric thermoelectric gel.
[0035] Example 10 The difference between this embodiment and embodiment 9 is that the stirring time at room temperature in S1 and S2 is 6 hours, and the other process steps and parameter settings are the same as those in embodiment 9.
[0036] Embodiment 11 S1. preparing a lower layer gel: uniformly mixing Bi2Te3 powder and bacterial cellulose dispersion to obtain a mixed solution 1, wherein the contents of bismuth telluride and bacterial cellulose in the mixed solution 1 are 10wt% and 60wt%, respectively; then adding a crosslinking agent glutaraldehyde to the mixed solution 1, wherein the amount of glutaraldehyde is 10wt% of the bacterial cellulose content in the mixed solution 1; stirring at room temperature for 4h to promote the gelation process and form a gel; pouring the formed gel into a mold having a length of 5cm, a width of 3cm, and a height of 2cm to obtain a lower layer gel; and the thickness of the lower layer gel is 1cm; S2, preparing the upper gel: PEDOT, MXene (Ti3AlC2) and bacterial cellulose dispersion are mixed evenly to obtain a mixed solution 2, in which the contents of PEDOT, MXene (Ti3AlC2) and bacterial cellulose are 2wt%, 1.5wt% and 60wt%, respectively; then, a crosslinking agent glutaraldehyde is added to the mixed solution 2, and the amount of glutaraldehyde is 10wt% of the bacterial cellulose content in the mixed solution 2; the mixture is stirred at room temperature for 4h to promote the gelation process and form a gel; the gel is poured onto the lower gel in the mold described in S1 to form an upper gel with a thickness of 1cm, and an asymmetric double-layer gel is obtained; S3, preparing a double-layer aerogel precursor: freezing the asymmetric double-layer gel for 30 hours using an ultra-low temperature freezing technique at -80°C to make it solid, thereby forming a double-layer aerogel precursor; S4. Preparation of asymmetric thermoelectric gel: Using vacuum freeze-drying technology, the double-layer aerogel precursor is dried and solidified for 48 hours to remove moisture in the precursor and obtain an asymmetric thermoelectric gel.
[0037] Example 12 The difference between this embodiment and embodiment 11 is that the temperature of the ultra-low temperature freezing technology in S3 is -40°C, and the remaining process steps and parameter settings are the same as those in embodiment 11.
[0038] Example 13 S1. Prepare the lower gel: Bi2Te3 powder and bacterial cellulose dispersion are mixed evenly to obtain a mixed solution 1, wherein the contents of bismuth telluride and bacterial cellulose in the mixed solution 1 are 15wt% and 60wt%, respectively; then, a crosslinking agent polyethylene glycol diglycidyl ether is added to the mixed solution 1, and the amount of polyethylene glycol diglycidyl ether is 10wt% of the bacterial cellulose content in the mixed solution 1; the mixture is stirred at room temperature for 4h to promote the gelation process and form a gel; the formed gel is poured into a mold with a length of 5cm, a width of 3cm, and a height of 2cm to obtain a lower gel; the thickness of the lower gel is 1cm; S2, prepare the upper gel: PEDOT, MXene (Ti3AlC2) and bacterial cellulose dispersion are mixed evenly to obtain mixed solution 2, in which the contents of PEDOT, MXene (Ti3AlC2) and bacterial cellulose are 2wt%, 1.5wt% and 60wt%, respectively; then, polyethylene glycol diglycidyl ether, a crosslinking agent, is added to the mixed solution 2, and the amount of polyethylene glycol diglycidyl ether is 10wt% of the bacterial cellulose content in the mixed solution 2; the mixture is stirred at room temperature for 4h to promote the gelation process and form a gel; the gel is poured onto the lower gel in the mold described in S1 to form an upper gel with a thickness of 1cm, and an asymmetric double-layer gel is obtained; S3, preparing a double-layer aerogel precursor: using -60°C ultra-low temperature freezing technology to freeze the asymmetric double-layer gel for 24 hours to make it solid, thereby forming a double-layer aerogel precursor; S4. Preparation of asymmetric thermoelectric gel: Using vacuum freeze-drying technology, the double-layer aerogel precursor is dried and solidified for 48 hours to remove moisture in the precursor and obtain an asymmetric thermoelectric gel.
[0039] Embodiment 14 The difference between this embodiment and embodiment 13 is that the ultra-low temperature freezing time in S3 is 48 hours, and the remaining process steps and parameter settings are the same as those in embodiment 13.
[0040] Embodiment 15 S1. Prepare the lower gel: Bi2Te3 powder and bacterial cellulose dispersion are mixed evenly to obtain a mixed solution 1, wherein the contents of bismuth telluride and bacterial cellulose in the mixed solution 1 are 15wt% and 60wt%, respectively; then, a crosslinking agent polyethylene glycol diglycidyl ether is added to the mixed solution 1, and the amount of polyethylene glycol diglycidyl ether is 10wt% of the bacterial cellulose content in the mixed solution 1; the mixture is stirred at room temperature for 4h to promote the gelation process and form a gel; the formed gel is poured into a mold with a length of 5cm, a width of 3cm, and a height of 2cm to obtain a lower gel; the thickness of the lower gel is 1cm; S2, prepare the upper gel: PEDOT, MXene (Ti3AlC2) and bacterial cellulose dispersion are mixed evenly to obtain mixed solution 2, in which the contents of PEDOT, MXene (Ti3AlC2) and bacterial cellulose are 2wt%, 1.5wt% and 60wt%, respectively; then, polyethylene glycol diglycidyl ether, a crosslinking agent, is added to the mixed solution 2, and the amount of polyethylene glycol diglycidyl ether is 10wt% of the bacterial cellulose content in the mixed solution 2; the mixture is stirred at room temperature for 4h to promote the gelation process and form a gel; the gel is poured onto the lower gel in the mold described in S1 to form an upper gel with a thickness of 1cm, and an asymmetric double-layer gel is obtained; S3, preparing a double-layer aerogel precursor: freezing the asymmetric double-layer gel for 30 hours using an ultra-low temperature freezing technique at -60°C to make it solid, thereby forming a double-layer aerogel precursor; S4. Preparation of asymmetric thermoelectric gel: Using vacuum freeze-drying technology, the double-layer aerogel precursor is dried and solidified for 24 hours to remove moisture in the precursor and obtain an asymmetric thermoelectric gel.
[0041] Example 16 The difference between this embodiment and embodiment 15 is that the vacuum freeze-drying time in S4 is 72 hours, and the remaining process steps and parameter settings are the same as those in embodiment 15.
[0042] Comparative Example 1 S1. Preparation of a single-layer gel: Bi2Te3 powder and a bacterial cellulose dispersion are uniformly mixed to obtain a mixed solution, wherein the contents of Bi2Te3 and bacterial cellulose in the mixed solution are 15wt% and 60wt%, respectively; then, a cross-linking agent, polyethylene glycol diglycidyl ether, is added to the mixed solution, wherein the amount of polyethylene glycol diglycidyl ether is 10wt% of the bacterial cellulose content in the mixed solution; the mixture is stirred at room temperature for 4h to promote the gelation process and form a gel; the formed gel is poured into a mold having a length of 5cm, a width of 3cm, and a height of 2cm to obtain a single-layer gel having a thickness of 2cm; S2: preparing a single-layer aerogel precursor: freezing the single-layer gel for 30 hours using an ultra-low temperature freezing technique at -60°C to make it solid, thereby obtaining a single-layer aerogel precursor; S3. Preparation of thermoelectric gel: Using vacuum freeze-drying technology, the single-layer aerogel precursor is dried and solidified for 48 hours to remove moisture in the precursor and obtain a single-layer thermoelectric gel.
[0043] The SEM image of the thermoelectric gel prepared in this comparative example is shown in FIG. Figure 3As shown, it can be seen that the microstructure surface of the thermoelectric gel in this comparative example is denser than that of the asymmetric thermoelectric gel prepared in Example 1. This dense morphology cannot form a uniform network structure due to the lack of a porous structure, and the thermoelectric performance cannot be improved.
[0044] Comparative Example 2 S1. Preparation of a single-layer gel: PEDOT, MXene (Ti3AlC2) and bacterial cellulose dispersion are uniformly mixed to obtain a mixed solution, in which the contents of PEDOT, MXene (Ti3AlC2) and bacterial cellulose are 2wt%, 1.5wt% and 60wt%, respectively. Then, a cross-linking agent, polyethylene glycol diglycidyl ether, is added to the mixed solution, and the amount of polyethylene glycol diglycidyl ether is 10wt% of the bacterial cellulose content in the mixed solution. The mixture is stirred at room temperature for 4 hours to promote the gelation process and form a gel. The gel is poured into a mold with a length of 5 cm, a width of 3 cm and a height of 2 cm to obtain a single-layer gel with a thickness of 2 cm. S2. Preparation of a single-layer aerogel precursor: freezing the gel for 48 hours using an ultra-low temperature freezing technique at -60°C to make it solid, thereby obtaining a single-layer aerogel precursor; S3. Preparation of thermoelectric gel: Using vacuum freeze-drying technology, the single-layer aerogel precursor is dried and solidified for 48 hours to remove moisture in the precursor and obtain thermoelectric gel.
[0045] The SEM image of the thermoelectric gel prepared in this comparative example is shown in FIG. Figure 4 As shown, it can be seen that the microstructure of the thermoelectric gel prepared in this comparative example has a certain network structure compared with that in comparative example 1, but compared with the asymmetric thermoelectric gel prepared in example 1, its porous structure is not as much as that in example 1. In addition, the aerogel in this comparative example is a single-layer structure, so although the aerogel in this comparative example has a certain network structure, its thermoelectric performance cannot be greatly improved, and the thermoelectric conversion efficiency is still low.
[0046] Comparative Example 3 S1. Preparation of a single-layer gel: PEDOT, MXene (Ti3AlC2), Bi2Te3 powder and bacterial cellulose dispersion are uniformly mixed to obtain a mixed solution, wherein the mass fractions of PEDOT, MXene (Ti3AlC2), Bi2Te3 powder and bacterial cellulose in the mixed solution are 2wt%, 1.5wt%, 15wt% and 60wt%, respectively. Then, a cross-linking agent, polyethylene glycol diglycidyl ether, is added to the mixed solution, and the amount of polyethylene glycol diglycidyl ether is 10wt% of the bacterial cellulose content in the mixed solution. The mixture is stirred at room temperature for 4h to promote the gelation process and form a gel. The gel is poured into a mold with a length of 5cm, a width of 3cm and a height of 2cm to obtain a single-layer gel with a thickness of 2cm. S2. Preparation of a single-layer aerogel precursor: freezing the single-layer gel for 48 hours using an ultra-low temperature freezing technique at -60°C to make it solid, thereby obtaining a single-layer aerogel precursor; S3. Preparation of thermoelectric gel: Using vacuum freeze-drying technology, the single-layer aerogel precursor is dried and solidified for 48 hours to remove moisture in the precursor and obtain thermoelectric gel.
[0047] Comparative Example 4 S1. Prepare the lower gel: Bi2Te3 powder and bacterial cellulose dispersion are mixed evenly to obtain a mixed solution 1, wherein the mass fractions of bismuth telluride and bacterial cellulose in the mixed solution 1 are 5wt% and 60wt%, respectively; then, a crosslinking agent epichlorohydrin is added to the mixed solution 1, and the amount of epichlorohydrin is 10wt% of the bacterial cellulose content in the mixed solution 1; the mixture is stirred at room temperature for 4h to promote the gelation process and form a gel; the formed gel is poured into a mold with a length of 5cm, a width of 3cm, and a height of 2cm to obtain a lower gel; the thickness of the lower gel is 1cm; S2, prepare the upper gel: PEDOT, MXene (Ti3AlC2) and bacterial cellulose dispersion are mixed evenly to obtain mixed solution 2, in which the mass fractions of PEDOT, MXene (Ti3AlC2) and bacterial cellulose are 1wt%, 1.5wt% and 60wt%, respectively, and then add crosslinking agent epichlorohydrin to the mixed solution 2, the amount of epichlorohydrin is 10wt% of the bacterial cellulose content in the mixed solution 2, stir at room temperature for 4h to promote the gelation process, form a gel, pour the gel onto the lower gel in the mold described in S1, form an upper gel with a thickness of 1cm, and obtain an asymmetric double-layer gel; S3, preparing a double-layer aerogel precursor: freezing the asymmetric double-layer gel for 30 hours using an ultra-low temperature freezing technique at -60°C to make it solid, thereby forming a double-layer aerogel precursor; S4. Preparation of asymmetric thermoelectric gel: Using vacuum freeze-drying technology, the double-layer aerogel precursor is dried and solidified for 48 hours to remove moisture in the precursor and obtain an asymmetric thermoelectric gel.
[0048] Comparative Example 5 S1. Prepare the lower layer gel: Bi2Te3 powder and bacterial cellulose dispersion are mixed evenly to obtain a mixed solution 1, wherein the mass fractions of bismuth telluride and bacterial cellulose in the mixed solution 1 are 15wt% and 60wt%, respectively; then, a crosslinking agent epichlorohydrin is added to the mixed solution 1, and the amount of epichlorohydrin is 10wt% of the bacterial cellulose content in the mixed solution 1; the mixture is stirred at room temperature for 4h to promote the gelation process and form a gel; the formed gel is poured into a mold with a length of 5cm, a width of 3cm, and a height of 2cm to obtain a lower layer gel; the thickness of the lower layer gel is 1cm; S2, prepare the upper gel: PEDOT, MXene (Ti3AlC2) and bacterial cellulose dispersion are mixed evenly to obtain mixed solution 2, in which the mass fractions of PEDOT, MXene (Ti3AlC2) and bacterial cellulose are 0.5wt%, 1.5wt% and 60wt%, respectively, and then add crosslinking agent epichlorohydrin to the mixed solution 2, the amount of epichlorohydrin is 10wt% of the bacterial cellulose content in the mixed solution 2, stir at room temperature for 4h to promote the gelation process, form a gel, and pour the gel onto the lower gel in the mold described in S1 to form an upper gel with a thickness of 1cm, and obtain an asymmetric double-layer gel; S3, preparing a double-layer aerogel precursor: freezing the asymmetric double-layer gel for 30 hours using an ultra-low temperature freezing technique at -60°C to make it solid, thereby forming a double-layer aerogel precursor; S4. Preparation of asymmetric thermoelectric gel: Using vacuum freeze-drying technology, the double-layer aerogel precursor is dried and solidified for 48 hours to remove moisture in the precursor and obtain an asymmetric thermoelectric gel.
[0049] Comparative Example 6 S1. Prepare the lower layer gel: Bi2Te3 powder and bacterial cellulose dispersion are mixed evenly to obtain a mixed solution 1, wherein the mass fractions of bismuth telluride and bacterial cellulose in the mixed solution 1 are 15wt% and 60wt%, respectively; then, a crosslinking agent epichlorohydrin is added to the mixed solution 1, and the amount of epichlorohydrin is 10wt% of the bacterial cellulose content in the mixed solution 1; the mixture is stirred at room temperature for 4h to promote the gelation process and form a gel; the formed gel is poured into a mold with a length of 5cm, a width of 3cm, and a height of 2cm to obtain a lower layer gel; the thickness of the lower layer gel is 1cm; S2, prepare the upper gel: PEDOT, MXene (Ti3AlC2) and bacterial cellulose dispersion are mixed evenly to obtain mixed solution 2, in which the mass fractions of PEDOT, MXene (Ti3AlC2) and bacterial cellulose are 1wt%, 0.1wt% and 60wt%, respectively, and then add crosslinking agent epichlorohydrin to the mixed solution 2, the amount of epichlorohydrin is 10wt% of the bacterial cellulose content in the mixed solution 2, stir at room temperature for 4h to promote the gelation process, form a gel, pour the gel onto the lower gel in the mold described in S1, form an upper gel with a thickness of 1cm, and obtain an asymmetric double-layer gel; S3, preparing a double-layer aerogel precursor: freezing the asymmetric double-layer gel for 30 hours using an ultra-low temperature freezing technique at -60°C to make it solid, thereby forming a double-layer aerogel precursor; S4. Preparation of asymmetric thermoelectric gel: Using vacuum freeze-drying technology, the double-layer aerogel precursor is dried and solidified for 48 hours to remove moisture in the precursor and obtain an asymmetric thermoelectric gel.
[0050] Comparative Example 7 S1. Prepare the lower gel: Bi2Te3 powder and bacterial cellulose dispersion are mixed evenly to obtain a mixed solution 1, wherein the mass fractions of bismuth telluride and bacterial cellulose in the mixed solution 1 are 15wt% and 30wt%, respectively; then, a crosslinking agent epichlorohydrin is added to the mixed solution 1, and the amount of epichlorohydrin is 10wt% of the bacterial cellulose content in the mixed solution 1; the mixture is stirred at room temperature for 4h to promote the gelation process and form a gel; the formed gel is poured into a mold with a length of 5cm, a width of 3cm, and a height of 2cm to obtain a lower gel; the thickness of the lower gel is 1cm; S2, prepare the upper gel: PEDOT, MXene (Ti3AlC2) and bacterial cellulose dispersion are mixed evenly to obtain mixed solution 2, in which the mass fractions of PEDOT, MXene (Ti3AlC2) and bacterial cellulose are 1wt%, 1.5wt% and 30wt%, respectively, and then add crosslinking agent epichlorohydrin to the mixed solution 2, the amount of epichlorohydrin is 10wt% of the bacterial cellulose content in the mixed solution 2, stir at room temperature for 4h to promote the gelation process, form a gel, pour the gel onto the lower gel in the mold described in S1, form an upper gel with a thickness of 1cm, and obtain an asymmetric double-layer gel; S3, preparing a double-layer aerogel precursor: freezing the asymmetric double-layer gel for 30 hours using an ultra-low temperature freezing technique at -60°C to make it solid, thereby forming a double-layer aerogel precursor; S4. Preparation of asymmetric thermoelectric gel: Using vacuum freeze-drying technology, the double-layer aerogel precursor is dried and solidified for 48 hours to remove moisture in the precursor and obtain an asymmetric thermoelectric gel.
[0051] The thermoelectric conversion performance of the thermoelectric gel prepared in Examples 1 to 16 and Comparative Examples 1 to 7 was tested, and the specific performance parameters tested were conductivity, Seebeck coefficient and power factor. The resistivity of the thermoelectric gel was tested using a ST2258C multifunctional digital four-probe tester, and the reciprocal of the resistivity was taken as the conductivity σ. The Seebeck coefficient was Figure 5 The schematic diagram shown in the figure is used for testing. The middle block part is the thermoelectric gel prepared in the embodiment or the comparative example. The lower end of the block part is heated to form a temperature difference ΔT between the upper and lower ends of the aerogel. The upper and lower ends of the aerogel are connected to a 34461A digital multimeter by wires to test the voltage difference ΔV. Finally, according to the formula , the Seebeck coefficient S of the thermoelectric gel is obtained. The dark horizontal line in the middle of the thermoelectric gel is caused by the edge of the lower heater projected onto the thermoelectric gel, which has no effect on the performance test. The power factor calculation formula is PF=σS 2PF stands for power factor, which is the product of conductivity and Seebeck coefficient. The test results of conductivity, Seebeck coefficient and power factor are shown in Table 1.
[0052] Table 1 Test results of thermoelectric conversion performance of aerogels prepared in Examples 1 to 16 and Comparative Examples 1 to 7
[0053] It can be seen from the data in Table 1 that the conductivity of the asymmetric thermoelectric gel prepared in Examples 1 to 16 is between 129.24 and 191.22 S / cm, and the conductivity is relatively high, indicating that electrons can move more smoothly in the aerogel material, which is beneficial to the extraction of electrical energy generated by thermoelectric conversion. In the thermoelectric conversion process, when Bi2Te3 absorbs heat to generate thermoelectric charges, the high conductivity channels constructed by MXene and PEDOT in the upper aerogel can quickly collect and conduct these charges, reducing the loss of charges, thereby improving the thermoelectric conversion efficiency.
[0054] The Seebeck coefficient of the asymmetric thermoelectric gel prepared in Examples 1 to 16 ranges from 32.87 to 49.52 μV / K. The Seebeck coefficient is relatively high, which means that under the same temperature difference, the aerogel materials prepared in Examples 1 to 16 can generate a larger voltage, that is, have a stronger thermoelectric conversion capability. When the Bi2Te3 in the lower layer of aerogel is heated by a heat source, the asymmetric thermoelectric gel provided by the present invention can more effectively convert heat into electrical energy. The power factor of the asymmetric thermoelectric gel prepared in Examples 1 to 16 is between 16.88 and 36.84 μW / (m·K 2 ), the power factor is high, indicating that the asymmetric thermoelectric gel prepared in Examples 1 to 16 generates a large amount of electrical power under a unit temperature gradient, which means that its thermoelectric conversion performance is better.
[0055] In contrast, Comparative Example 1 uses only Bi2Te3 and bacterial cellulose to prepare a single-layer thermoelectric gel. Figure 3From the microstructure, the aerogel surface is more dense, without porous structure, and cannot form a uniform network structure. In addition, it lacks MXene or PEDOT, and does not have an efficient charge conduction network like the asymmetric thermoelectric gel of the present invention. Charge conduction is blocked and the conductivity is reduced. At the same time, the dense microstructure is not conducive to the uniform transfer of heat in the aerogel, which makes the Seebeck coefficient of the aerogel low and the thermoelectric conversion efficiency low. In this case, the thermoelectric charge generated by Bi2Te3 is difficult to be effectively derived, and thermal energy cannot be fully converted into electrical energy. The thermoelectric gel prepared in Comparative Example 2 does not contain Bi2Te3, but only PEDOT, MXene and bacterial cellulose. Due to the lack of the key thermoelectric conversion material Bi2Te3, and the failure to form a structure in which the upper and lower layers in the present invention are coordinated, effective thermoelectric conversion cannot be achieved. Although PEDOT and MXene can construct a charge conduction network, there is no source of thermoelectric conversion, resulting in extremely low conductivity, Seebeck coefficient and power factor, and thermal energy cannot be converted into electrical energy. Thermoelectric performance cannot be reflected, and the thermoelectric conversion efficiency is very low. The thermoelectric gel prepared in Comparative Example 3 contains Bi2Te3, PEDOT and MXene, but the thermoelectric gel has a single-layer structure, so that the Bi2Te3, PEDOT and MXene materials cannot perform thermoelectric conversion between the upper and lower layer structures as in the present invention. Each material can fully play its own role and play a synergistic role at the same time. Therefore, the thermoelectric gel prepared in Comparative Example 3 cannot achieve effective division of labor in thermoelectric conversion and charge conduction, and the respective role levels of Bi2Te3, PEDOT and MXene are affected, resulting in low conductivity, Seebeck coefficient and power factor of the aerogel, and low thermoelectric conversion efficiency.
[0056] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing an asymmetric thermoelectric gel, characterized in that: The following steps are involved: S1, preparing a lower layer gel: mixing bismuth telluride powder and bacterial cellulose dispersion evenly to obtain a mixed solution 1, wherein the mixed solution 1 contains bismuth telluride and bacterial cellulose, then adding a cross-linking agent to the mixed solution 1, stirring at room temperature to form a gel, and pouring the gel into a mold to obtain a lower layer gel; S2, preparing an upper gel: uniformly mixing poly(3,4-ethylenedioxythiophene), MXene and bacterial cellulose dispersion to obtain a mixed solution 2, wherein the mixed solution 2 contains poly(3,4-ethylenedioxythiophene), MXene and bacterial cellulose, and then adding a crosslinking agent to the mixed solution 2, stirring at room temperature to form a gel, and pouring the gel onto the lower gel in the mold described in S1 to form an upper gel, thereby obtaining an asymmetric double-layer gel; S3, preparing a double-layer aerogel precursor: using ultra-low temperature freezing technology to treat an asymmetric double-layer gel to obtain a double-layer aerogel precursor; S4. Preparation of asymmetric thermoelectric gel: using vacuum freeze drying technology to dry and solidify the double-layer aerogel precursor to obtain an asymmetric thermoelectric gel; The asymmetric thermoelectric gel is obtained by treating an asymmetric double-layer gel with ultra-low temperature freezing technology and vacuum freeze drying technology, and the upper layer gel and the lower layer gel in the asymmetric double-layer gel are prepared with different materials.
2. The preparation method according to claim 1, characterized in that: The contents of bismuth telluride and bacterial cellulose in the mixed solution 1 of S1 are 10-20wt% and 50-80wt%, respectively.
3. The preparation method according to claim 1, characterized in that: The contents of poly(3,4-ethylenedioxythiophene), MXene and bacterial cellulose in the mixed solution 2 of S2 are 1~3wt%, 0.5~2wt% and 50~80wt%, respectively.
4. The method for preparing the asymmetric thermoelectric gel according to claim 1, characterized in that: The stirring time in S1 and S2 is 3~6h.
5. The preparation method according to claim 1, characterized in that: The cross-linking agents in S1 and S2 are chemical reagents that promote the cross-linking reaction between bacterial cellulose molecules.
6. The preparation method according to claim 1, characterized in that: The amount of cross-linking agent used in S1 is 10 wt % of the bacterial cellulose content in the mixed solution 1 of S1; the amount of cross-linking agent used in S2 is 10 wt % of the bacterial cellulose content in the mixed solution 2 of S2.
7. The preparation method according to claim 1, characterized in that: The ultra-low temperature freezing technology in S3 has a temperature of -80~-40℃ and a time of 24~48h.
8. The preparation method according to claim 1, characterized in that: The time for drying and solidification treatment using vacuum freeze-drying technology in S4 is 24 to 72 hours.
9. An asymmetric thermoelectric gel, characterized in that: Prepared by the method according to any one of claims 1 to 8.
10. An application of the asymmetric thermoelectric gel according to claim 9, characterized in that: Used as thermoelectric material in the field of thermoelectric conversion.
Citation Information
Patent Citations
A method for preparing composite aerogel thermoelectric materials
CN109301060B
Sandwich-type cement-based thermoelectric functional material and preparation method thereof
CN103427014A
Preparation method for composite aerogel thermoelectric material
CN109301060A
Preparation method of flexible Mxene / PEDOT:PSS composite thermoelectric material
CN113224231A
Preparation method of flexible recoverable thermoelectric thin film
CN113517385A